Pengaruh Literasi Keuangan dan Kualitas Kinerja Pelaporan Keuangan Terhadap Keberlanjutan Usaha Mikro, Kecil, dan Menengah di Desa Pereng, Kabupaten Prambanan - Devi Natalia; Ika Wulandari (Income Journal: Accounting, Management and Economic Research, 2024)
The observational data that highlights the significance of financial reporting for businesses especially as a way to account for the financial transactions that occur within them was the driving force for this study. The goal of this study is to ascertain how financial literacy and the performance quality of financial reports affect business sustainability in Micro, Small and Medium Enterprises in Pereng Village. Business continuity is the dependent variable that is quantitative study, whereas financial literacy and the effectiveness of financial statement quality are the independent variables. In this study, the population that became the subject of research as a whole was used as a sample in a saturated sampling approach, having a 50 responder sample size. Primary data were used to create the study's data. This data collection technique is an interview and distributes questionnaires. Data from multiple linear analysis studies were displayed using the Statistical Package for the Social Sciences (SPSS) version 25 application. The findings indicated that the level of financial statement performance has a favorable and substantial effect on business continuity while financial literacy has no bearing on it. With these findings, it is expected that the government, acting as a regulator, academia, the private sector, acting as a catalyst, and the community, acting as an enabler, will contribute significantly to the growth of financial literacy in MSMEs in Pereng Village, Prambanan District